ANALISIS QOS (QUALITY OF SERVICE) PADA JARINGAN INTERNET (STUDI KASUS: FAKULTAS TEKNIK UNIVERSITAS TANJUNGPURA) - Yanto, Yanto (Jurnal Fakultas Teknologi Informasi, 2013)
Abstract-- Faculty of Engineering University of Tanjungpura as one of the government educational institutions take an active role in the intellectual life of the nation, requiring infrastructure and take advantage of advances in information technology to achieve optimal results, such as the internet. The development of the Internet and network lately has made IP (Internet Protocol), which is the backbone of networking-based TCP / IP is rapidly becoming obsolete. QoS (Quality of Service) is technology that applied to the WAN (Wide Area Network) that allows network administrators to be able to handle a variety of effects due to congestion (congestion) on the traffic flow of packets in the network. QoS parameters are delay / latency, jitter, packet loss, throughput, MOS, echo cancellation and PDD. QoS parameters that measured are delay, jitter, throughtput, packet loss and MOS (Mean Opinion Score). Result of measurement of QoS parameters that have been made, value delay was 3.39 with good index, jitter was 1.50 with bad index, throughput was 1 with bad index, packet loss was 4 with very good index and MOS was 2.34 with less than good index, so the average total of QoS parameters was 2.45 with index Enough and with itâs percentage was 61.25% in the TIPHON standard, thus it can be concluded that the internet of Faculty of Engineering University of Tanjungpura belonging to unsatisfactory standard based on the standard of TIPHON (Joesman 2008) with a rating of < 95%.Keywords-- Internet, QoS, QoS Parameters, TIPHONÂ